The Environmental Aspect of "Making People Rich as the Top Priority" in China: a Marxian Perspective - Malte Faber; Thomas Petersen (University of Heidelberg, Department of Economics, 2012)
Income inequality in China is severe; measured by the Gini-coefficient it amounted to 0.46 in 2011; wealth distribution is even worse with 0.61. These disparities led to a major shift in emphasis of politics in general and of the Five-Year Plan for National Economic and Social Development by the National People's Congress in particular. While previously the strategy of the Five-Year Plans had been "Making the nation [our emphasis] rich as top priority", this was changed to "Making people [our emphasis] rich as top priority" in the 12th Five-Year Plan (2011-2015), enacted in March 2011.The strategic change from "nation" to "people" indicates that the political decision-makers in China accepted the aim of a fair income distribution as a political issue of great importance. In this paper, richness is defined in the political-philosophical tradition as the right measure for one's own needs and wants; only its environmental aspect is focused on in this study. The development of the Chinese environmental conditions is compared with the German ones and the former's future outlook is judged optimistically because of the achievements in the last five years. However, the complexity and fragility of the environmental system will within a decade confront Chinese politicians with the same problems as it does right now in Germany. In order to provide a solution addressing this development, this paper analyzes what Karl Marx had to say on the long-run dynamics of the economic system. He saw poverty as a necessary yet unintended consequence of the capitalistic system and used this insight as a "precision tool for the study of social change" (Elster 1986), which can also be employed to examine the unintended repercussions of economic activity on nature. Marx, who studied environmental and resource issues in detail, thought that the inventiveness of the capitalistic system would finally overcome all of them in the course of time. In view of the fact that three billion people on earth still have a backlog demand to satisfy basic needs and in addition a further three billion are expected to be born until 2050, the future of the natural environmental conditions looks somber. If it is not possible to decouple economic growth from ensuing environmental strain, Marx may well be right after all in his prediction that the capitalistic system will collapse, although in quite a different manner than he thought. This being the case we take recourse to the thoughts of one of the influential intellectual German figures, to Romano Guardini. He foresaw changes in the self-perception of humankind and in the comprehension of nature. These imply a shift in the ethos of government as well, which would in turn pose three great challenges to politics: (i) understanding nature in a new light, (ii) listening to what drives human hearts, and (iii) governing according to law.
urn:nbn:de:bsz:16-opus-131893
Keywords: Q56; B14; B51; D31; D63; D90; O13; P26; 330; Wealth; Distribution; PR China; Environment; Sustainabilit y; Wachstumspolitik; Umweltbelastung; Umverteilung; Kapitalismus; Marxismus; Umweltpolitik; Nachhaltige Entwicklung; China